2018
DOI: 10.35663/amp.2018.351.514
|View full text |Cite
|
Sign up to set email alerts
|

Mitos, creencias y prácticas en cuidadores de niños con asma respecto al tratamiento con inhaladores en Chiclayo, Perú - 2013

Abstract: Objetivos: Describir, analizar y explorar los mitos, creencias y prácticas de cuidadores de niños con asma en relación al tratamiento con inhaladores en la provincia de Chiclayo durante el año 2013. Material y métodos: Estudio cualitativo, de perspectiva explicativa, con base en la etnografía; se realizaron grupos focales y triangulación de la información; participaron 20 cuidadores de niños asmáticos, distribuidos en cuatro grupos focales y siete médicos pediatras; fueron captados mediante muestreo por conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“… 12 The myths regarding side effects of asthma medications were very similar to those reported by caregivers in Peru and Colombia. 22 24 This is a common barrier to asthma care, as for other chronic diseases, leading to poor adherence to medications. 12–15 17 18 Poor adherence to long-term asthma medications and the fear of side effects is common in low, 22 24 and high-income settings 9–15 alike, and is also independent of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 12 The myths regarding side effects of asthma medications were very similar to those reported by caregivers in Peru and Colombia. 22 24 This is a common barrier to asthma care, as for other chronic diseases, leading to poor adherence to medications. 12–15 17 18 Poor adherence to long-term asthma medications and the fear of side effects is common in low, 22 24 and high-income settings 9–15 alike, and is also independent of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“… 22 24 This is a common barrier to asthma care, as for other chronic diseases, leading to poor adherence to medications. 12–15 17 18 Poor adherence to long-term asthma medications and the fear of side effects is common in low, 22 24 and high-income settings 9–15 alike, and is also independent of ethnicity. 12 In addition, HCPs also reported that caregivers used the health system only when acutely ill.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Algunas de las creencias más comunes en Perú sobre el tratamiento con inhaladores para el asma son que producen trastornos cardíacos, causan dependencia, ocasionan cambios de conducta, limitan o detienen el crecimiento normal, originan alteraciones osteomusculares, perturban el sistema nervioso, producen sobrepeso, obesidad e hinchazón, reduce el rendimiento y deteriora el coeficiente intelectual, generan asma. 11 Existen muchos efectos desencadenantes, como el aire frío, las emociones fuertes (miedo, ira) o el ejercicio físico. Tenemos muchos medicamentos que también pueden desencadenar ataques de asma, como la aspirina y otros antiinflamatorios no esteroideos o los betabloqueantes (fármacos utilizados en el tratamiento de la hipertensión arterial, algunas enfermedades cardiacas o la migraña); y pese a la existencia de tratamientos eficaces, las encuestas realizadas a pacientes nos muestran de Keiry Altamirano Nureña, et al manera determinada evidencias indicativas de un control deficiente del asma en muchos países y el desconocimiento de las causales.…”
Section: Introductionunclassified